Carbon release from Large Igneous Province magmas estimated from trace element-gas correlations - Black, Benjamin A; Aiuppa, Alessandro (Volcanica, 2023)
Large Igneous Provinces (LIPs) facilitate massive transfers of CO2 and other volatiles from the mantle to atmosphere, contributing to past global warming and environmental disruption. However, the scale and evolution of magmatic CO2 fluxes during these events remain uncertain due to the tendency of CO2 to degas deep in magmatic systems. Here we estimate LIP CO2 using an approach based on an observed correlation between gas CO2/S ratios and trace elements in volcanic rocks. We apply this method to a compilation of published geochemical data for tholeiitic LIP lavas and to a new major and trace element dataset for alkaline rocks from the Siberian Traps. Our results indicate that CO2/S and therefore CO2 in tholeiitic and alkaline magma suites from LIPs span 1–2 orders of magnitude, emphasizing that changing CO2 concentrations can combine with magma flux to drive strong variations in CO2 release through the evolution of LIP magmatism.